1994
DOI: 10.3382/ps.0730627
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intermittent Periods of High Environmental Temperature on Broiler Performance Responses to Sources of Methionine Activity

Abstract: The objective of these experiments was to study the effect of intermittent high temperature (IHT) on performance of broilers fed different sources of methionine activity. Two 20-d experiments were conducted in which individually caged 28-d-old cockerels were exposed to a 5-d period of constant high temperature (HT, 30 to 32 C) followed by an equal period of thermoneutral (TN) temperatures (22 C) with the 10-d temperature cycle repeated twice. Birds held at 22 C were TN controls. Grower diets contained 3,275 kc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 15 publications
1
17
1
1
Order By: Relevance
“…In vitro experiments have shown that HS influenced D-Met absorption as compared to L-Met absorption (Knight et al, 1994). This fact would be disadvantageous to DLM-fed birds in comparison to HMB-fed birds, when they enter into the thermoneutral period.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro experiments have shown that HS influenced D-Met absorption as compared to L-Met absorption (Knight et al, 1994). This fact would be disadvantageous to DLM-fed birds in comparison to HMB-fed birds, when they enter into the thermoneutral period.…”
Section: Introductionmentioning
confidence: 99%
“…While differences in absorption, metabolism, organ distribution and/or clearance between HMB and DLM (Saunderson 1985(Saunderson , 1987Dibner 2003) may also play a role, changes in the efficacy of either source of Met to fulfill the birds' requirements for total sulfur amino acids during HS cannot be discounted. Dibner et al (1992) and Knight et al (1994) measured the absorption of DLM in vitro as affected by HS in broilers. These authors concluded that the intestinal uptake of the D isomer of methionine was negatively impaired during HS mainly due to a significant reduction in the energy-and Na-dependent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In a subsequent experiment, these authors observed even greater growth depression in heat-stressed birds fed diets supplemented with D-methionine vs. those with L-Met suggesting that the impaired absorption for D-methionine mediated the lower performance of broilers fed DLM under tropical environments. However, the effects of HS on the in vitro uptake of these Met sources found by Dibner et al (1992) and Knight et al (1994) correspond to situations of short exposures to high temperatures and these effects have not been evaluated in vivo or in birds subjected to prolonged HS ( > 2 wk).…”
mentioning
confidence: 99%
See 2 more Smart Citations